Religijny i społeczny status kobiet w tradycjach o Abrahamie (Rdz 11,27–25,18) - Dziadosz, Dariusz (Studia Pastoralne, 2026)
Abraham is the link figure throughout these narratives, but in several of the individual stories he is in the background, with the main focus being on another, whether Sarah, Hagar, Lot, Lot’s wife and daughters, Abraham’s servant or Rebekah. These narratives leave the reader in no doubt about the key part played by women in Israel’s early history. The writer is certainly aware of women’s interests and concerns and seems to be making a conscious effort to make sure that these interests and concerns are brought out within the text. There are a number of occasions where the account, although not always the characters it portrays, indicates an understanding of and attitude toward women that does not reflect the worldview of the society depicted. Sarai is introduced alongside Abram in Genesis 11, and although God’s call and God’s promises are described as coming to Abram, it is clear that Sarai was with him from the beginning to the end.